Pelaksanaan Reformasi Birokrasi dalam Pengembangan Sumber Daya Manusia di Dinas Pemuda dan Olahraga Kota Padang - Nurmasari, Hizkia Putri; Jumiati, Jumiati (Lembaga Yasin AlSys, 2024)
This research aims to determine the implementation of bureaucratic reform in human resource development at the The Youth and Sports Service of the city of Padang. This research was conducted using a qualitative approach with a descriptive method, in determining informants the researcher used a purposive sampling method. Data collection techniques are carried out using interviews, observation and documentation. From the research results, it can be seen that the implementation of bureaucratic reform in human resource development at the Padang City Youth and Sports Service has gone well. However, it can also be noted that employee skills and expertise are still inadequate, therefore explaining how important it is to provide training for State Civil Apparatus for agencies that need it. The Padang City Youth and Sports Service has carried out bureaucratic reform in the aspect of human resource reform. Human resource development through (1) employee recruitment such as employee recruitment (2) competency-based employee development such as job descriptions for structural and non-structural employees, employee job grading, employee position competency document standards, employee position competency profile maps and training (3) assessment of individual employee performance through employee work targets (SKP) (4) development of a personnel information system through an employee data base. However, in the process of implementing bureaucratic reform in developing human resources at the Padang City Youth and Sports Department, there are obstacles, namely the position placement is not in accordance with the level of education, there is still a lack of adequate infrastructure, there is still a lack of provision of inadequate training for civil servant from the regional government. local. One of the efforts made by the Padang City Youth and Sports Department is to collaborate with the regional government and provide training for civil servant.